A Meta-Analysis of the Success Rate of Helicobacter pylori Therapy in Canada - Christopher Rodgers; Sander Veldhuyzen van Zanten (Canadian Journal of Gastroenterology)
BACKGROUND AND AIM: Helicobacter pylori treatment success rates have varied. A systematic review of the success rate of anti-H pylori therapy in Canada was performed.